Drivers of prohibited natural resource collection in Chitwan National Park, Nepal. (7th June 2022) - Yabiku, Scott T; Sullivan, Abigail; York, Abigail M; Zhao, Qunshan; Glick, Jennifer E; Hall, Sharon J; Ghimire, Dirgha J; An, Li
Summary: Protected areas (PAs) are critical for achieving conservation, economic and development goals, but the factors that lead households to engage in prohibited resource collection in PAs are not well understood. We examine collection behaviours in community forests and the protected Chitwan National Park in Chitwan, Nepal. Our approach incorporates household and ecological data, including structured interviews, spatially explicit data on collection behaviours measured with computer tablets and a systematic field survey of invasive species. We pair our data with a framework that considers factors related to a household's demand for resources, barriers to prohibited resource collection, barriers to legal resource collection and alternatives to resource collection. The analysis identifies key drivers of prohibited collection, including sociodemographic variables and perceptions of an invasive plant ( Mikania micrantha ). The social-ecological systems approach reveals that household perceptions of the presence of M. micrantha were more strongly associated with resource collection decisions than the actual ecologically measured presence of the plant. We explore the policy implications of our findings for PAs and propose that employing a social-ecological systems approach leads to conservation policy and scientific insights that are not possible to achieve with social or ecological approaches alone.